Van Giffen's Dogs: Cranial Osteometry of Iron Age to Medieval Period Dogs from the Northern Netherlands. (20th February 2018) - Scheele, E.E.; Çakırlar, C.
This paper presents biometric data from a collection of 488 dogs skulls originating from 58 (archaeological) sites in the northern Netherlands dating from the Iron Age to the Medieval Period. The crania were originally collected and documented in the early 20 th century by Prof. Albert Egges van Giffen, one of the pioneers of Dutch archaeology and archaeozoology. The 'De honden van Van Giffen' project has transcribed, translated and digitized the original handwritten records and tables, supplementing the information with new photographs of a selection of the specimens, and made the dataset openly accessible for researchers worldwide oneasy.dans.knaw.nl . This dataset is an unparalleled treasure trove of canid osteometric data with sustainable reuse potential for research into dog domestication, the evolution of dog breeds, and cranial variability in canids.